PARTISIPASI KELUARGA ANGGOTA BINA KELUARGA BALITA (BKB) DALAM PENGASUHAN DAN TUMBUH KEMBANG ANAK USIA 0-6 TAHUN - NFN Oktriyanto (Jurnal Kependudukan Indonesia, 2016)
The age of 0-6 years is the most critical period in determining the quality of life in the future. By participating in the activities of Bina Keluarga Balita (BKB), families are expected to be  able to provide the best care for the growth and development of the children. The purpose of this analysis is to determine: 1) The differences between  families member of BKB and families are not member BKB on their participation in growth and development of children age 0- 6 years.  2) Factors that affect the family's participation in growth and development of children age 0- 6 years.  This analysis used secondary data from Performance Indicator Survey of The National Medium Term Development Plan in Population and Family Planning Proram Year 2015. The survey was conducted in 34 provinces throughout Indonesia. Respondents used are families with children age  0-6 years, with the total number of respondents 16 172 families. The results showed that the family’s participation in the growth and development of children age  0-6 years is better in the family members of BKB than families who do not participate in BKB from all aspects (physical, mental and social). The results of logistic regression analysis showed that the level of family welfare, maternal age, maternal education, maternal work status, family who have children aged 0-6 years, and family participation in BKB group has significant effect on family participation in growth and development of children age 0- 6 years